การวิเคราะห์โครงสร้างต้นทุนการผลิตของการปลูกข้าว กลุ่มวิสาหกิจชุมชนศูนย์เมล็ดพันธุ์ข้าว ตำบลออนใต้ อำเภอสันกำแพง จังหวัดเชียงใหม่ / An Analysis of the Production Cost Structure of Rice Planting at the Ontai Rice Seed Small and Micro Community Enterprise in Sankamphaeng District, Chiang Mai - Pikul Pongklang, พิกุล พงษ์กลาง / (Journal of Community Development Research (Humanities and Social Sciences), 2017)
การวิจัยนี้เป็นการวิจัยปฏิบัติการแบบมีส่วนร่วม มีวัตถุประสงค์เพื่อวิเคราะห์ความรู้เกี่ยวกับโครงสร้างต้นทุนการผลิตของการปลูกข้าว โดยการศึกษาประชากรที่เป็นสมาชิกกลุ่มวิสาหกิจชุมชนศูนย์เมล็ดพันธุ์ข้าว ตำบลออนใต้ อำเภอสันกำแพง จังหวัดเชียงใหม่ จำนวน 28 ราย งานวิจัยนี้ใช้แบบทดสอบเป็นเครื่องมือในการรวบรวมข้อมูลและการจัดเวทีประชาคมเป็นเครื่องมือในการพัฒนา มีการวิเคราะห์ข้อมูลเชิงปริมาณโดยใช้สถิติเชิงพรรณนาวิเคราะห์ค่าทางสถิติ ได้แก่ การแจกแจงความถี่ ค่าร้อยละ และค่าเฉลี่ย และข้อมูลเชิงคุณภาพโดยตรวจสอบความครบถ้วนของข้อมูลที่ได้ตามขอบเขตเนื้อหาและวัตถุประสงค์ของการวิจัย ระยะเวลาในการศึกษาตั้งแต่เดือนพฤศจิกายน 2556 ถึงเดือนกุมภาพันธ์ 2558 ผลการวิจัย พบว่า สมาชิกกลุ่มวิสาหกิจชุมชนศูนย์เมล็ดพันธุ์ข้าว สามารถวิเคราะห์โครงสร้างต้นทุนผลิตของการปลูกข้าวที่ประกอบด้วย วัตถุทางตรง ค่าแรงงานทางตรง และค่าใช้จ่ายการผลิต โดยเฉลี่ยอยู่ในเกณฑ์ค่อนข้างต่ำ และจากการเข้าร่วมเวทีประชาคม สมาชิกกลุ่มวิสาหกิจชุมชนสามารถวิเคราะห์โครงสร้างต้นทุนการผลิตของการปลูกข้าว เพื่อคำนวณผลกำไรขาดทุนจากการปลูกข้าวได้ ส่งผลให้เพิ่มความสามารถในการบริหารจัดการต้นทุนและนำไปสู่การลดต้นทุนการผลิตในที่สุด      This research was a participatory action research that aimed to investigate knowledge relating to cost structure of rice planting. Population of this research included 28 farmers, who were members of the Ontai rice seed small and micro community enterprise in Sankamphang district, Chiang Mai. Questionnaire was conducted as a research tool for collecting data and community forum was arranged for development. Several descriptive statistics were applied, such as frequency; percentage; mean and qualitative data were analyzed by checking the completeness of data according to the content and objectives of research. This research was conducted from November 2013 to February 2015. Results indicated that the members of community enterprise of rice seed center had averagely low ability to analyze cost structure of rice planting which consisted of cost of direct material, direct labor costs, and overhead costs. According to community forum, this study found that participants were able to analyze cost structure of production cost for calculating profit/ loss of rice planting, which enhanced their ability to managing the cost and led to cost reduction.
Keywords: โครงสร้างต้นทุนการผลิต การปลูกข้าว วิสาหกิจชุมชนศูนย์เมล็ดพันธุ์ข้าว; Production Cost Structure, Rice Planting, Rice Seed Small and Micro Community Enterprise